Preoperative cognitive training improves postoperative cognitive function: a meta-analysis and systematic review of randomized controlled trials - Zhao, Li; Guo, Yiping; Zhou, Xuelei; Mao, Wei; Li, Linji (Frontiers in Neurology, 2024)
Background: Postoperative cognitive dysfunction (POCD) and postoperative delirium (POD) are common post-surgical complications that often lead to prolonged hospitalization, reduced quality of life, increased healthcare costs, and increased patient mortality. We conducted a meta-analysis to evaluate the effects of preoperative cognitive function training on postoperative cognitive function. Methods: PubMed, Cochrane Library, Embase, Web of Science, ClinicalTrials, China National Knowledge Infrastructure, Wanfang Database, VIP Database, and Chinese Biomedical Literature Database were searched for randomized controlled trials comparing the effects of preoperative cognitive function training and conventional preoperative measures on postoperative cognitive function. The search period spanned from the establishment of the databases to March 31, 2023. The primary outcomes were the incidence of POCD and POD. Results: Eleven randomized controlled trials involving 1045 patients were included. The results of the meta-analysis showed that, compared to the control group, preoperative cognitive function training significantly reduced the incidence of POCD (RR=0.38, P<0.00001), and there was no statistically significant difference in the incidence of POD (P=0.3). Cognitive function training significantly improved postoperative cognitive function scores compared with the control group (MD=1.92, P=0.001). In addition, two studies reported that 10% of the patients in the cognitive training group completed a pre-set training duration. Conclusion: Cognitive function training significantly reduced the incidence of POCD; however, there was no significant difference in the incidence of POD. Preoperative cognitive function training should be promoted and emphasized as a simple, economical, and practical method of improving postoperative cognitive function.